Management of Leaf Gall Forming Insect, Trioza obsoleta Buckton (Homoptera: Psyllidae) on Diospyros melanoxylon Roxb. in Chhattisgrah - Meshram, P. B.; Mawai, Nahar Singh; Malviya, R. K. (Indian Forester, 2016)
Leaf gall forming insect, Trioza obsoleta (Buckton) is one of the key insect pest, known as ’pox’ disease’ which deteriorates the leaf quality causing heavy losses in economic terms. It causes galls in leaves which render unsuitable for bidi wrapper. The present investigation has been undertaken with the objective standardization of management practices for D. melanoxylon leaf gall forming insect. Nine different locations viz. Littipara (Gariyabad, East Raipur), Lohattar (East Bhanupratppur, Kanker), Morga (Kathghora, Bilaspur), Kotadol (Korea), Kota, Bharni (Bilaspur), Raipur, Chichola (Rajnandgaon) and Kawardha in Chhattisgarh state, India were conducted for monitoring the status of T. obsoleta. The incidence of T. obsoleta varies from 50-60 per cent were recorded. The field experiments were conducted during 2011-12 and 2012-13 at Morga, (Range - Kendai, Forest Division Katghora, Chhattisgarh, India). The results revealed that the treatment of synthetic pyrethroid, deltamethrin (decis) 2.5 EC. @ 0.002 per cent followed by cypermethrin 20 E.C. @ 0.03 per cent was found to be most effective against T. obsoleta. The first pruning including control fire in first week of March was found to be most effective and suitable for minimizing the incidence of T. obsoleta, and increasing the weight and area of leaves after 45 days of pruning.